How a Stay-at-Home Father Plays a Role in Family Resilience? - Fatimah, Fatimah; Daryanto, Eko (UI Scholars Hub, 2026)
One of the impacts of modernization is the loss of barriers between job and particular gender. This also happens in the family unit, more specifically in the role of husband and wife. The husband's job which is identical to earn money and the wife's job is to manage the household should be able to be done more flexibly according to family conditions. This adaptation process is needed in order to strengthen family resilience. Non-traditional family composition that usually consist of a stay-at-home father and a working mother can be used as a family adaptation strategy. This study uses the results of stay-at-home father interviews in 4 online media to be applied to Resilient Family Prominent Protective and Recovery Factor Characteristics and the Family Resilience Framework. This study reveals that family resilience among stay-at-home fathers is shaped by shared belief systems, open communication, and flexible role arrangements. Fathers and their partners adapt to challenges through mutual support, teamwork, and a strong sense of purpose. External support networks and the rejection of rigid gender norms further enhance overall family well-being and stability.